Combined use of FNAC &genexpert MTB/rifin the Rapid Diagnosis of TB Lymphadenitis – a Case Report - Dr. SHANTHI RAMESH; Dr. SINDHU M; Dr. SUNDARI S (International Journal of Pharma and Bio Sciences, 2016)
India is the global capital of Tuberculosis with an estimated 2.2 million active cases of TB as on 2016. Molecular diagnostic tests like GeneXpert MTB/RIF helps in early diagnosis and monitoring response to therapy including resistant tuberculosis and this will go a long way in augmenting TB control in India. A 17 years old girl presented with history of low grade fever and weight loss for 3 weeks. Examination revealed a solitary, 2 cm by 2cm, painless lymph node palpable in the right supra clavicular region. System examination was normal. Her father was treated for tuberculosis 2 years ago. Investigation showed a positive Mantoux of 20mm and the fine needle aspiration cytology (FNAC) specimen sent for GeneXpert MTB/RIF test confirmed the diagnosis of tuberculosis. The patient was started on anti-tuberculosis treatment. She is doing well on follow up as evidenced by the regression of the lymph node. She has gained weight and her appetite is good. Childhood TB accounts about 10% of all tuberculosis. The burden of TB in children is a reflection of the pool of infectious adult pulmonary tuberculosis cases in the community. Extrapulmonary tuberculosis appears to be increasing in children. Among the extrapulmonary manifestations, lymphadenopathy is the most common. The GeneXpert MTB/RIF assay is a major breakthrough in diagnosis of tuberculosis. The introduction of GeneXpert MTB/RIF as initial diagnostic test for TB in the RNTCP program has significantly increased the case-notification rates of all bacteriologically confirmed TB by 39% and rifampicin-resistant TB case by fivefold. WHO recommends GeneXpert (Xpert MTB/RIF) to be used as the initial diagnostic test in patients suspected of having tuberculosis. From this case report we want to highlight the fact that the combined use of fine needle aspiration and GeneXpert provides a rapid diagnosis in a child presenting with lymphadenopathy.